Bout duration and number of players of soccer small-sided games affect perceived enjoyment, physiological responses, and technical-tactical performance - Farhani, Z.; Hammami, R.; Gene-Morales, J.; Chortane, S. G.; Bouassida, A.; Juesas, A.; Colado, J. C. (Science and Medicine in Football, 2022)
Purpose: To compare perceived enjoyment (PE), % of heart rate peak (%HRpeak), blood lactate (La), rating of perceived exertion (RPE), and technical-tactical performance of soccer players after four-a-side (4vs4) and three-a-side (3vs3) small-sided games (SSGs) with goalkeepers. Methods: Sixteen males (20.7±0.7years; experience: 6.9±1.2years) completed and were measured after six sessions of SSGs (one twelve-minute bout (1x12), two six-minute bouts (2x6), and three four-minute bouts (3x4), both 3vs3 and 4vs4). Repeated measurements ANOVA evaluated significant differences (p =0.05). Results: There was higher PE for 1×12 compared to 2×6 (effect sizes [ES]=1.53 [3vs3 and 4vs4]) and 3×4 (ES=3.13 [4vs4] and 4.16 [3vs3]). Continuous bout duration (1x12) was characterized by a significantly greater percentage of successful passes compared to 2×6 (ES=2.57 [4vs4] and 1.79 [3vs3]) and 3×4 (ES=2.14 [4vs4] and 1.73 [3vs3]), and minor ball loss rate (2x6: ES=2.14 [4vs4] and 1.11 [3vs3]; 3x4: ES=2.11 [4vs4] and 1.57 [3vs3]). The percentage of successful tackles was only significantly greater for 1×12 in 4vs4 (ES=0.83 [2x6] and 0.86 [3x4]) and successful duels in 3vs3 (ES=1.41 [2x6] and 1.43 [3x4]). Significantly greater %HRpeak for 1×12 compared to 2×6 (ES=1.02 [4vs4] and 0.81 [3vs3]) and 3×4 (ES=1.04 [4vs4] and 0.99 [3vs3]) was observed, La differences were only significant in 3vs3 (ES=1.60 [2x6] and 1.30 [3x4]). Greatest RPE were encountered in 3×4 (4vs4) and 1×12 and 3×4 (3vs3). Significant differences existed between the 3vs3 and 4vs4 designs with a non-clear pattern of better results for neither of both. Conclusion: Therefore, coaches should consider longer continuous bouts when programming SSGs-based training to significantly increase PE, technical-tactical performance, and training load.